Persepsi Mahasiswa terhadap Learning Management System (LMS): Pengaruh Lokasi, Perangkat dan Analisis Kepuasan Mahasiswa - Andi Saputra; Susiana Susiana (BPSDMP Kominfo Jakarta, 2021)
LMS is one of the many online learning models that are applied as online learning media in universities. This model is believed to be able to overcome the high cost of internet packages incurred by students when using online meeting applications. This study aims to measure the level of student satisfaction and perceived with the Ilearn application, with the Moodle platform, which is used by Andalas University. Student perceptions were measured using 6 categories, namely: (a) student interaction with lecturers; (b) student interactions with other students; (c) internet devices and access; (d) motivation to learn); (e) participation during lectures; and (f) perception and absorption of material. Measurement of the level of satisfaction is calculated using descriptive statistical methods. These variables were analyzed based on gender, study period, location of residence, and the instruments used using the one way ANOVA method. This study concluded that the level of satisfaction felt by students as a whole was quite low, especially for the items of internet access, focus and concentration of lectures, and active participation in lectures. It was also concluded that there was no significant effect of gender, location, and the tools used on the level of satisfaction and uptake of recovery materials. Meanwhile, the study period had a significant effect on the level of satisfaction felt by students